Battery device case and method of manufacturing the same
Patent Information
- Application Number
- CN202610147554.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-02-02
AI Technical Summary
[0003]现有的电池箱体为了提高对内部结构的防护能力,会增设防撞结构,然后造成电池箱体的重量增加,且防冲击能力有限无法达到需求
[0015]本申请实施例的电池装置的箱体及其制备方法,纤维毡层、交错纤维层和单向纤维层的质量密度梯度设置能够有效分散冲击能量,避免缓冲结构出现局部断裂,从而提高电池装置箱体的抗冲击性,同时这种梯度结构能够在保证缓冲性能和结构强度的前提下,兼顾箱体的轻量化需求。
Smart Images

Figure CN122051527B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of batteries, and in particular relates to a battery device housing and its manufacturing method. Background Technology
[0002] The battery unit is the core electrical energy device for realizing energy storage, charge and discharge management, and safe output. It is the energy core of new energy vehicles and energy storage systems. The battery casing is the core carrier, protective shell, and integration platform of the battery unit. All battery cells and control systems of the battery unit are integrated into the casing, which is the foundation for the battery unit to achieve mechanical safety, sealing safety, and thermal management.
[0003] To improve the protection of the internal structure, existing battery enclosures often incorporate anti-collision structures, which increases the weight of the battery enclosure and limits its impact resistance, failing to meet the required standards. Summary of the Invention
[0004] This application provides a battery device housing and its manufacturing method, which can achieve lightweight housing and improve impact resistance.
[0005] On one hand, embodiments of this application provide a battery device housing, including: a housing body and a buffer structure, the buffer structure being connected to the periphery of the housing body; the buffer structure includes a cross-linked matrix and multiple functional fiber layers, the cross-linked matrix being filled between the functional fiber layers and the fiber structure being permeated and connected to the functional fiber layers, the multiple functional fiber layers including a fiber felt layer, an interlaced fiber layer and a unidirectional fiber layer, the interlaced fiber layer being stacked along the thickness direction on both sides of the fiber felt layer, the unidirectional fiber layer being stacked along the thickness direction on both sides of the interlaced fiber layer, and the mass density of the fiber felt layer, the interlaced fiber layer and the unidirectional fiber layer increasing sequentially layer by layer.
[0006] In some alternative embodiments, the mass density of each layer in the fiber felt layer, the interwoven fiber layer, and the unidirectional fiber layer is in the range of 0.8 g / cm³. 3 Up to 3.5g / cm 3 .
[0007] In some alternative embodiments, the mass density of the fiber felt layer ranges from 1.25 g / cm³. 3 Up to 0.8 g / cm 3 The mass density of the interwoven fiber layer ranges from 1.5 g / cm³. 3 Up to 1.8 g / cm 3 The mass density of the unidirectional fiber layer ranges from 1.85 g / cm³. 3 Up to 3.5g / cm 3 .
[0008] In some alternative embodiments, the thickness of the cushioning structure ranges from 1 mm to 3 mm; and / or, the thickness of the fiber felt layer ranges from 0.4 mm to 0.6 mm; the thickness of the interlaced fiber layer ranges from 0.5 mm to 0.7 mm; and the thickness of the unidirectional fiber layer ranges from 0.6 mm to 0.8 mm.
[0009] In some alternative embodiments, the volume fraction of the surface porosity of the buffer structure is between 1% and 2%, and the pore size is less than or equal to 0.1 micrometers.
[0010] On the other hand, this application also provides a method for preparing the casing of the above-mentioned battery device, comprising: pre-impregnating multiple functional fiber layers in a crosslinking matrix solution and pre-curing them, so that the crosslinking matrix crosslinks and fills the fiber structures between each functional fiber layer and permeates and connects to each functional fiber layer, forming multiple functional fiber semi-cured layers, the multiple functional fiber semi-cured layers including a fiber felt semi-cured layer, an interlaced fiber semi-cured layer and a unidirectional fiber semi-cured layer with progressively increasing mass density; laying the fiber felt semi-cured layer, the interlaced fiber semi-cured layer and the unidirectional fiber semi-cured layer in a mold in a laying sequence, wherein the laying sequence includes the interlaced fiber semi-cured layer being stacked along the thickness direction on both sides of the fiber felt semi-cured layer, and the unidirectional fiber semi-cured layer being stacked along the thickness direction on both sides of the interlaced fiber semi-cured layer; secondary curing, in which the crosslinking matrix of the fiber felt semi-cured layer, the interlaced fiber semi-cured layer and the unidirectional fiber semi-cured layer flows and permeates each other, and is compacted and connected under a preset pressure to form a buffer structure; and connecting the buffer structure to the periphery of the casing body to form the casing of the battery device.
[0011] In some optional embodiments, before prepregning multiple functional fiber layers in a crosslinking matrix solution and precuring them, so that the crosslinking matrix crosslinks and fills the fiber structures between and permeates and connects to the functional fiber layers to form multiple functional fiber semi-cured layers, the method further includes: subjecting multiple functional fiber layers to plasma treatment in a mixed gas environment of inert gas and oxygen.
[0012] In some alternative embodiments, the volume ratio of inert gas to oxygen is 4:1; and / or, the inert gas is argon.
[0013] In some alternative embodiments, the pre-curing temperature is 60-80°C and the pre-curing time is 15-25 minutes.
[0014] In some alternative embodiments, before connecting the buffer structure to the periphery of the housing to form the battery device housing, the method further includes: spraying an anti-corrosion coating onto the outer peripheral surface of the buffer structure.
[0015] The battery device housing and its manufacturing method in this application embodiment utilize a mass density gradient setting of fiber felt layer, interlaced fiber layer and unidirectional fiber layer to effectively disperse impact energy and avoid local breakage of the buffer structure, thereby improving the impact resistance of the battery device housing. At the same time, this gradient structure can meet the lightweight requirements of the housing while ensuring buffer performance and structural strength. Attached Figure Description
[0016] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly introduced below. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a top view of the housing of a battery device according to some embodiments of this application; Figure 2 An example is shown. Figure 1 Cross-sectional view of the buffer structure; Figure 3 Show Figure 2 Cross-sectional view along the AA direction; Figure 4 A flowchart illustrating an example of a method for manufacturing the housing of a battery device according to some embodiments of this application; Figure 5 This is a flowchart illustrating another example of a method for manufacturing the housing of a battery device according to some embodiments of this application.
[0018] Explanation of reference numerals in the attached figures: 100. Box body; 200. Buffer structure; 201. Fiber felt layer; 202. Interlaced fiber layer; 203. Unidirectional fiber layer. Detailed Implementation
[0019] The features and exemplary embodiments of various aspects of this application will be described in detail below. To make the objectives, technical solutions, and advantages of this application clearer, the application will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only intended to explain this application and not to limit it. For those skilled in the art, this application can be implemented without some of these specific details. The following description of the embodiments is merely to provide a better understanding of this application by illustrating examples.
[0020] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus that includes the element.
[0021] The battery pack's casing anti-collision structure is the core line of defense for the battery pack's mechanical safety. Through structural design, it absorbs collision energy, disperses collision force, and resists deformation of the casing, ultimately preventing external impacts from squeezing or damaging the internal battery cells. For example, the anti-collision structure of the four sides of the battery pack casing in new energy vehicles needs to have high impact resistance to cope with collision risks. In related technologies, anti-collision structures often use steel or aluminum alloy frames. Metal anti-collision frames are heavy, affecting vehicle energy efficiency. There are also anti-collision structures that combine composite materials with metal, but these structures are prone to delamination and cannot meet high-impact requirements.
[0022] In view of this, the present application provides a battery device housing, which can effectively disperse impact energy by setting a mass density gradient of fiber felt layer, interlaced fiber layer and unidirectional fiber layer, avoid local breakage of the buffer structure, thereby improving the impact resistance of the battery device housing. At the same time, this gradient structure can take into account the lightweight requirements of the housing while ensuring buffer performance and structural strength.
[0023] The following combination Figures 1 to 5 This paper provides a detailed description of the battery device housing and its preparation method.
[0024] like Figures 1 to 3 As shown, this application embodiment provides a battery device housing, including a housing body 100 and a buffer structure 200. The buffer structure 200 is connected to the periphery of the housing body 100. The buffer structure 200 includes a cross-linked matrix and multiple functional fiber layers. The cross-linked matrix is filled between the functional fiber layers and permeates and connects to the fiber structure in each functional fiber layer. The multiple functional fiber layers include a fiber felt layer 201, an interlaced fiber layer 202, and a unidirectional fiber layer 203. The interlaced fiber layer 202 is stacked along the thickness direction on both sides of the fiber felt layer 201, and the unidirectional fiber layer 203 is stacked along the thickness direction on both sides of the interlaced fiber layer 202. The mass density of the fiber felt layer 201, the interlaced fiber layer 202, and the unidirectional fiber layer 203 increases sequentially layer by layer.
[0025] The housing 100 serves as the main supporting structure of the battery device housing, supporting the buffer structure 200 and the internal battery components. There is only one housing 100; in the overall structure of the battery device, the housing 100 is the sole main load-bearing component, ensuring stable support for the internal components and the integrity of the overall structure. Exemplarily, the housing 100 can be a cuboid, cube, cylinder, or irregular polygon, etc. For example, a cuboid housing 100 adapts to the installation requirements of most square battery modules. Its regular internal space facilitates the arrangement and fixing of individual battery cells, and the rounded corners of the cuboid structure reduce stress concentration.
[0026] In some examples, the material of the housing body 100 can be aluminum alloy, stainless steel, high-strength engineering plastic or carbon fiber composite material. For example, the aluminum alloy housing body 100 has the characteristics of light weight, high strength and good thermal conductivity, which can effectively reduce the overall weight of the battery device and facilitate heat dissipation.
[0027] In one example, the housing body 100 is located at the outermost layer of the battery device, and its interior forms a receiving cavity for placing components such as battery cells and battery management system. The buffer structure 200 is connected to its periphery and is set around the outer periphery of the housing body 100 to form all-round protection.
[0028] The buffer structure 200 is used to absorb external impact energy, protect the main body 100 and the internal battery components, and prevent battery damage caused by impact. The number of buffer structures 200 can be one, two, or four, or more.
[0029] In one example, the shape of the buffer structure 200 is adapted to the peripheral shape of the box body 100. When the box body 100 is a cuboid, the buffer structure 200 is a frame structure that fits the four sides of the cuboid.
[0030] In some examples, the connection between the buffer structure 200 and the box body 100 can be achieved by bonding, bolting, snap-fitting, etc. Specifically, bonding the buffer structure 200 to the box body 100 involves applying a layer of adhesive to the peripheral surface of the box body 100, then attaching the buffer structure 200 to the peripheral surface of the box body 100. After the adhesive cures, a firm connection between the buffer structure 200 and the box body 100 is achieved. This connection method is convenient to operate, provides a tight connection, and does not damage the structural integrity of the box body 100 and the buffer structure 200, making it suitable for most scenarios.
[0031] For example, the buffer structure 200 is located around the periphery of the box body 100, and can cover all surfaces around the box body 100, as well as key stress-bearing surfaces around the box body 100, to ensure that it can effectively absorb energy when subjected to external impact and protect the box body 100.
[0032] The cross-linked matrix serves as the bonding and filling component of the buffer structure 200, connecting multiple functional fiber layers into a single unit. The cross-linked matrix has no fixed, independent shape; it conforms perfectly to the gaps between the functional fiber layers and the interfiber spaces within the functional fiber layers, exhibiting an irregular shape after filling.
[0033] In some examples, the crosslinking matrix material can be epoxy resin, polyurethane, silicone rubber, or phenolic resin. As an example, a polyurethane crosslinking matrix has excellent elasticity and cushioning properties, which can further enhance the impact absorption capacity of the cushioning structure 200.
[0034] In some examples, there are three functional fiber layers: a fiber felt layer 201, a cross-fiber layer 202, and a unidirectional fiber layer 203, with each layer corresponding to the others. In some examples, there are five functional fiber layers: a cross-fiber layer 202 is placed on each side of the fiber felt layer 201, and a unidirectional fiber layer 203 is placed on the outside of each cross-fiber layer 202, forming a symmetrical stacked structure.
[0035] For example, the shape of the functional fiber layer is adapted to the overall shape of the buffer structure 200, and it is a sheet structure with the same size as the buffer structure 200.
[0036] The fiber felt layer 201, as the inner layer of the functional fiber layers, is used to initially absorb impact energy and acts as a buffer transition. It is located in the middle of multiple functional fiber layers and is the core transition layer of the entire functional fiber layer stacked structure. As an example, the fiber felt layer 201 has a sheet-like structure.
[0037] For example, the fiber felt layer 201 can be made of glass fiber felt, carbon fiber felt, or aramid fiber felt. Among these, glass fiber felt has a lower cost, good toughness and cushioning performance, and can effectively absorb low-frequency impact energy. The fiber felt layer 201 is located in the middle of multiple functional fiber layers, with interlaced fiber layers 202 on both sides. The fiber felt layer 201 has a uniform thickness and is tightly bonded to the interlaced fiber layers 202 on both sides, achieving a firm connection through a cross-linked matrix.
[0038] The interlaced fiber layer 202 serves as an intermediate transition layer among the functional fiber layers, used to transfer and disperse impact energy. Exemplarily, two interlaced fiber layers 202 are disposed on either side of the fiber felt layer 201, exhibiting a symmetrical distribution to ensure consistent performance on both sides of the buffer structure 200. As an example, the interlaced fiber layer 202 has a sheet-like shape.
[0039] In one example, the angle between the fiber bundles in the interlaced fiber layer 202 is ±45°.
[0040] In some examples, the material of the interwoven fiber layer 202 can be interwoven glass fiber cloth, interwoven carbon fiber cloth, or interwoven aramid fiber cloth, etc. As an example, interwoven aramid fiber cloth has excellent impact resistance and can withstand high-frequency impact loads.
[0041] The unidirectional fiber layer 203 serves as the outer layer of the functional fiber layer, bearing the main impact loads and enhancing the overall strength of the buffer structure 200. Two unidirectional fiber layers 203 are present, positioned on either side of the interlaced fiber layer 202, on the outermost side of the entire functional fiber layer stack structure, exhibiting a symmetrical distribution. As an example, the unidirectional fiber layer 203 has a sheet-like shape.
[0042] In one example, the buffer structure 200 is a hollow cuboid structure, and the unidirectional fiber layer 203 is stacked to cover the entire outer and inner surfaces of the buffer structure 200, ensuring that it can fully withstand external impacts.
[0043] For example, the material of the unidirectional fiber layer 203 can be unidirectional glass fiber cloth, unidirectional carbon fiber cloth, or unidirectional aramid fiber cloth, etc. The unidirectional fiber layer 203 is located on the outermost side of the entire functional fiber layer stacked structure. Its inner side is closely attached to the interlaced fiber layer 202, and its outer side is the outer surface of the buffer structure 200, which is in direct contact with the external environment and bears external impact loads.
[0044] Mass density refers to the mass per unit volume of the functional fiber layer. The fiber felt layer 201 has the lowest mass density, the interwoven fiber layer 202 has a higher mass density than the fiber felt layer 201, and the unidirectional fiber layer 203 has the highest mass density, forming a gradient distribution that gradually increases from the middle to both sides.
[0045] In some examples, the mass density gradient distribution is linearly increasing, that is, the mass density increment from the fiber felt layer 201 to the interwoven fiber layer 202 is consistent with the mass density increment from the interwoven fiber layer 202 to the unidirectional fiber layer 203, ensuring a smooth transition in the performance of the buffer structure 200.
[0046] In other examples, this gradient distribution is non-linearly increasing, meaning that the mass density increment from the interlaced fiber layer 202 to the unidirectional fiber layer 203 is greater than the mass density increment from the fiber felt layer 201 to the interlaced fiber layer 202, thus focusing on enhancing the strength of the outer layer of the buffer structure 200 to withstand greater impact loads.
[0047] In some examples, the fiber volume content of the buffer structure 200 is 50-60%.
[0048] In this embodiment, the gradient setting of the mass density of the fiber felt layer 201, the interlaced fiber layer 202, and the unidirectional fiber layer 203 can effectively disperse impact energy and prevent local breakage of the buffer structure 200, thereby improving the impact resistance of the battery device housing. At the same time, this gradient structure can meet the lightweight requirements of the housing while ensuring buffering performance and structural strength. Specifically, the fiber felt layer 201 with the lowest mass density serves as an intermediate transition layer, which can initially absorb impact energy and play a buffering role; the interlaced fiber layer 202 with a medium mass density can further transfer and disperse the impact energy absorbed by the fiber felt layer 201, avoiding energy concentration; the unidirectional fiber layer 203 with the highest mass density serves as the outer layer, which can withstand the main impact load and improve the overall strength of the buffer structure 200. The three layers work together to allow the impact energy to be absorbed and dispersed in layers, avoiding excessive local stress that could cause the buffer structure 200 to break, thereby protecting the housing body 100 and the internal battery components. Meanwhile, the gradient-set mass density allows for the rational allocation of material usage. High-density materials are used in critical stress areas to ensure strength, while low-density materials are used in transition areas to reduce weight, achieving a balance between impact resistance and lightweight design. The buffer structure reduces weight by 40%, improving vehicle range.
[0049] Furthermore, in some optional embodiments of this application, the mass density of each layer in the fiber felt layer 201, the interwoven fiber layer 202, and the unidirectional fiber layer 203 is all in the range of 0.8 g / cm³. 3 Up to 3.5g / cm 3 .
[0050] For example, the mass density of each functional fiber layer can be 0.8 g / cm³. 3 0.9g / cm 3 1g / cm 3 1.2g / cm 3 1.5g / cm 3 1.7g / cm 3 2g / cm 3 2.3g / cm 3 2.5g / cm 3 2.9g / cm 3 3g / cm 33.1g / cm 3 3.5g / cm 3 The range of one or more components in the composition. The mass density of the fiber felt layer 201, the interwoven fiber layer 202, and the unidirectional fiber layer 203 is all within 0.8 g / cm³. 3 Up to 3.5g / cm 3 Within a certain range, the mass density of the three substances increases sequentially layer by layer, forming a gradient distribution.
[0051] In one example, in the battery device of a new energy vehicle, where lightweighting is a high requirement and the device needs to withstand a certain amount of external impact, a fiber felt layer with a mass density of 1.0 g / cm³ can be selected. 3 The cross-fiber layer 202 has a mass density of 2.0 g / cm³. 3 The unidirectional fiber layer 203 has a mass density of 3.0 g / cm³. 3 It meets the requirements for lightweight design while ensuring good impact resistance.
[0052] In another example, in the battery device of an energy storage device, where the requirements for lightweighting are relatively low but the requirements for structural strength are high, a fiber felt layer with a mass density of 2.5 g / cm³ can be selected. 3 The cross-fiber layer 202 has a mass density of 3.0 g / cm³. 3 The unidirectional fiber layer 203 has a mass density of 3.5 g / cm³. 3 This ensures that it can withstand large impact loads.
[0053] In this embodiment, the mass density range of each layer in the fiber felt layer 201, the interwoven fiber layer 202, and the unidirectional fiber layer 203 is defined as 0.8 g / cm³. 3 Up to 3.5g / cm 3 This ensures that the mass density of each functional fiber layer is within a reasonable range. It avoids insufficient structural strength due to excessively low mass density, which would prevent the buffer structure 200 from effectively withstanding impact loads and thus cause it to break, affecting the protective performance of the battery pack enclosure. Conversely, it avoids excessively high mass density, which would increase the overall weight of the battery pack enclosure and violate the lightweight design principle. This mass density range provides a reasonable basis for selecting the mass density of each functional fiber layer, ensuring that the three layers form an effective mass density gradient, synergistically dispersing impact energy and improving impact resistance, while also considering the lightweight requirements of the enclosure. This allows the battery pack enclosure to possess both excellent protective performance and adaptability to the lightweight requirements of different scenarios.
[0054] Specifically, in some embodiments of this application, the mass density of the fiber felt layer 201 ranges from 1.25 g / cm³. 3 Up to 0.8 g / cm 3The mass density of the interwoven fiber layer 202 ranges from 1.5 g / cm³. 3 Up to 1.8 g / cm 3 The mass density of the unidirectional fiber layer 203 ranges from 1.85 g / cm³. 3 Up to 3.5g / cm 3 .
[0055] For example, the mass density of the fiber felt layer 201 can be 0.8 g / cm³. 3 0.9g / cm 3 1g / cm 3 1.2g / cm 3 1.25g / cm 3 One or more components of the range.
[0056] In some examples, the mass density of the fiber felt layer 201 is 0.8 g / cm³. 3 At this point, the fiber felt layer 201 is the lightest and has the best cushioning performance, maximizing the absorption of external impact energy and providing excellent buffering. It is suitable for scenarios with extremely high lightweight requirements and relatively mild external impacts, such as battery devices in small energy storage equipment. In some examples, the mass density of the fiber felt layer 201 is 1.0 g / cm³. 3 At this point, the fiber felt layer 201 combines buffering performance with a certain structural strength, absorbing impact energy while transferring some energy to the interlaced fiber layers 202 on both sides, achieving initial energy dispersion, suitable for conventional scenarios. In some examples, the mass density of the fiber felt layer 201 is 1.25 g / cm³. 3 At this point, the fiber felt layer 201 has relatively high structural strength and good buffering performance, and can withstand certain impact loads. It is suitable for scenarios with slightly larger external impacts, such as battery devices in new energy vehicles, and can effectively absorb the impact energy generated by bumps and minor collisions during vehicle operation.
[0057] For example, the mass density of the interlaced fiber layer 202 can be 1.5 g / cm³. 3 1.6g / cm 3 1.65g / cm 3 1.7g / cm 3 1.75g / cm 3 1.8g / cm 3 One or more components of the range.
[0058] In some examples, the mass density of the interwoven fiber layer 202 is 1.5 g / cm³. 3At this point, the interwoven fiber layer 202 is relatively lightweight, meeting the requirements for weight reduction while possessing good energy transfer and dispersion capabilities. It can evenly transfer the impact energy absorbed by the fiber felt layer 201 to the outer unidirectional fiber layer 203, avoiding energy concentration, making it suitable for scenarios where lightweighting is the priority. In some examples, the mass density of the interwoven fiber layer 202 is 1.65 g / cm³. 3 At this point, the structural strength and energy dispersion capability of the interwoven fiber layer 202 are at their optimal state, effectively transferring and dispersing impact energy. Simultaneously, it forms a reasonable gradient difference with the fiber felt layer 201 and the unidirectional fiber layer 203, ensuring stratified energy transfer, making it suitable for most conventional scenarios. In some examples, the mass density of the interwoven fiber layer 202 is 1.8 g / cm³. 3 At this point, the interlaced fiber layer 202 has high structural strength, stronger energy transfer and dispersion capabilities, and can withstand greater impact energy transfer. It is suitable for scenarios with large external impacts and can effectively protect the inner fiber felt layer 201 and the outer unidirectional fiber layer 203.
[0059] For example, the mass density of the unidirectional fiber layer 203 can be 1.85 g / cm³. 3 2g / cm 3 2.3g / cm 3 2.5g / cm 3 2.95g / cm 3 3g / cm 3 3.2g / cm 3 3.35g / cm 3 3.5g / cm 3 One or more components of the range.
[0060] In some examples, the mass density of the unidirectional fiber layer 203 is 1.85 g / cm³. 3 At this point, the unidirectional fiber layer 203 is relatively lightweight, meeting the requirements for weight reduction while maintaining a certain structural strength to withstand minor external impact loads. This makes it suitable for applications with low external impact, such as indoor energy storage devices. In some examples, the mass density of the unidirectional fiber layer 203 is 2.5 g / cm³. 3 At this point, the unidirectional fiber layer 203 exhibits high structural strength, capable of withstanding significant impact loads. It effectively protects the internal interwoven fiber layer 202 and fiber felt layer 201, preventing the buffer structure 200 from breaking. Simultaneously, its moderate weight balances lightweight design and protective performance, making it suitable for general applications. In some examples, the unidirectional fiber layer 203 has a mass density of 3.5 g / cm³. 3At this point, the unidirectional fiber layer 203 has the highest structural strength and can withstand extremely strong impact loads. It is suitable for extreme impact environments, such as energy storage devices in harsh outdoor environments or battery devices in heavy new energy vehicles. It can effectively resist the impact energy generated by strong external collisions and protect the box body 100 and the internal battery components.
[0061] In this embodiment, the low mass density range of the fiber felt layer 201 ensures that it can fully exert its buffering and absorption function, initially absorbing impact energy; the intermediate mass density range of the interlaced fiber layer 202 ensures that it can effectively transfer and disperse the impact energy absorbed by the fiber felt layer 201, achieving a smooth energy transition; the high mass density range of the unidirectional fiber layer 203 ensures that it can withstand the main impact load, improving the overall strength of the buffer structure 200. The three layers work together to more efficiently disperse impact energy and avoid excessive local stress that could cause the buffer structure 200 to break. At the same time, the mass density range of each layer has been optimized to minimize the weight of the buffer structure 200 while ensuring the functionality of each layer, further optimizing the lightweight effect of the battery device housing. This allows the housing to not only have excellent protective performance but also adapt to the lightweight requirements of different scenarios, enhancing the overall competitiveness of the battery device.
[0062] Specifically, in some embodiments of this application, the thickness of the buffer structure 200 ranges from 1 mm to 3 mm; and / or, the thickness of the fiber felt layer 201 ranges from 0.4 mm to 0.6 mm; the thickness of the interlaced fiber layer 202 ranges from 0.5 mm to 0.7 mm; and the thickness of the unidirectional fiber layer 203 ranges from 0.6 mm to 0.8 mm.
[0063] For example, the thickness can be a range consisting of one or more of 1 mm, 1.3 mm, 1.5 mm, 1.8 mm, 2 mm, 2.1 mm, 2.5 mm, 2.9 mm, and 3 mm. In one example, the thickness of the hollow cuboid buffer structure 200 is the wall thickness.
[0064] In some examples, the thickness of the buffer structure 200 is 2mm. In this case, the buffer structure 200 takes into account both buffer performance and lightweight requirements, and can effectively absorb conventional impact energy, protect the main body 100 and the internal battery components. It is suitable for most conventional scenarios, such as battery devices of new energy vehicles and indoor energy storage equipment.
[0065] The thickness of the fiber felt layer 201 ranges from 0.4 mm to 0.6 mm. This range is suitable for the fiber felt layer 201's function as an intermediate transition layer, primarily playing a role in buffering and absorbing impact energy. Its relatively thin thickness allows it to absorb impact energy while avoiding excessive space occupation, thus meeting the requirements of lightweight design. In some examples, the thickness of the fiber felt layer 201 is 0.5 mm. At this thickness, the buffering and absorption capacity and structural stability of the fiber felt layer 201 are at their optimal levels. It can effectively absorb impact energy while providing stable support for the interlaced fiber layers 202 on both sides, making it suitable for general applications.
[0066] The thickness of the interlaced fiber layer 202 ranges from 0.5 mm to 0.7 mm. This range is suitable for the interlaced fiber layer 202's function as an intermediate transition layer, primarily playing a role in energy transfer and dispersion. Its thickness is between that of the fiber felt layer 201 and the unidirectional fiber layer 203, ensuring smooth energy transfer while enhancing the overall strength of the buffer structure 200. In some examples, the thickness of the interlaced fiber layer 202 is 0.6 mm. At this thickness, the energy transfer, dispersion, and structural strength of the interlaced fiber layer 202 are at their optimal levels, effectively transferring and dispersing impact energy. Simultaneously, it forms a reasonable thickness combination with the fiber felt layer 201 and the unidirectional fiber layer 203, ensuring uniform stress distribution on the buffer structure 200, suitable for general scenarios.
[0067] The thickness of the unidirectional fiber layer 203 ranges from 0.6 mm to 0.8 mm. This range is suitable for the unidirectional fiber layer 203's function as an outer layer, primarily responsible for bearing impact loads and enhancing structural strength. Its relatively thick thickness ensures sufficient structural strength to withstand external impact loads. In some examples, the thickness of the unidirectional fiber layer 203 is 0.8 mm, at which point the structural strength of the unidirectional fiber layer 203 is highest, capable of withstanding extremely strong impact loads. This makes it suitable for extreme impact environments, effectively resisting the impact energy generated by strong external collisions and protecting the housing body 100 and internal battery components.
[0068] In this embodiment, by limiting the thickness range of the buffer structure 200 and each functional fiber layer, it is ensured that the thickness of the buffer structure 200 and each functional fiber layer is within a reasonable range. This avoids insufficient buffering performance due to excessive thickness, which would prevent effective absorption of impact energy and thus fail to protect the housing body 100 and the internal battery components. Simultaneously, it avoids excessive thickness leading to excessive weight of the buffer structure 200, increasing the overall weight of the battery device and violating the lightweight design concept. Specifically, limiting the thickness range of the buffer structure 200 ensures sufficient buffer space to effectively absorb impact energy and improve the impact resistance of the housing. Limiting the thickness range of each functional fiber layer ensures that each layer performs its corresponding function: the thickness of the fiber felt layer 201 ensures its buffering absorption effect, the thickness of the interwoven fiber layer 202 ensures its energy transfer and dispersion effect, and the thickness of the unidirectional fiber layer 203 ensures its ability to withstand impact loads. The combination of these three thicknesses, along with the mass density gradient, further optimizes the layered absorption and dispersion effect of impact energy, while minimizing the weight of the buffer structure 200, achieving the technical effect of lightweight housing.
[0069] Furthermore, in some alternative embodiments of this application, the volume fraction of the surface porosity of the buffer structure 200 is between 1% and 2%, and the pore size is less than or equal to 0.1 micrometers.
[0070] Porosity refers to the ratio of the volume of pores on the surface of buffer structure 200 to the total volume of the surface of buffer structure 200. Pore size refers to the maximum diameter of a single pore on the surface of buffer structure 200.
[0071] The surface porosity and pore size of the buffer structure 200 are controlled through its molding process and material selection. For example, during the curing process of the crosslinked matrix, the surface porosity and pore size of the buffer structure 200 can be adjusted by controlling the curing temperature, curing time, and preset pressure. Selecting suitable crosslinked matrix and functional fiber layer materials can also optimize the surface density of the buffer structure 200. Alternatively, plasma treatment or coating with a coupling agent can be applied to the functional fiber layer to increase the wettability of the crosslinked matrix.
[0072] Meanwhile, the limited surface porosity and pore size of the buffer structure 200 will not affect its buffering performance and structural strength. Because the porosity and pore size within this range are relatively small, they will not significantly impact the overall structure of the buffer structure 200. The functional fiber layer and the cross-linked matrix can still synergistically disperse impact energy and improve impact resistance, while also meeting the requirements for lightweight design. In practical applications, the surface porosity and pore size of the buffer structure 200 can be adjusted within this limited range according to the corrosion intensity of the specific scenario.
[0073] In this embodiment, by limiting the volume fraction of the surface porosity of the buffer structure 200 to 1% to 2% and the pore size to less than or equal to 0.1 micrometers, a dense structure can be formed on the surface of the buffer structure 200, effectively blocking external corrosive media, such as moisture, salt spray, and chemical ions, from entering the interior of the buffer structure 200. This avoids aging of the cross-linked matrix and corrosion and breakage of the functional fiber layer, while also preventing corrosive media from penetrating to the surface of the housing body 100 and causing corrosion of the housing body 100. This improves the corrosion resistance of the battery device housing and extends the service life of the housing.
[0074] refer to Figure 3 and Figure 4 As shown, this application embodiment also provides a method for manufacturing the housing of the battery device described in the above embodiments, comprising: S1: Prepreg multiple functional fiber layers in a crosslinking matrix solution and pre-cur them, so that the crosslinking matrix crosslinks and fills the fiber structure between each functional fiber layer and permeates and connects to each functional fiber layer, forming multiple functional fiber semi-cured layers. The multiple functional fiber semi-cured layers include fiber felt semi-cured layers, interlaced fiber semi-cured layers and unidirectional fiber semi-cured layers with progressively increasing mass density.
[0075] Functional fiber layer prepreg refers to a prepreg made by immersing a functional fiber layer in a crosslinking matrix solution, so that the crosslinking matrix solution uniformly covers the surface of the functional fiber layer and initially penetrates into the fiber structure of the functional fiber layer.
[0076] In some examples, the prepreg is implemented by methods such as immersion, spraying, and brushing. In some examples, the immersion method can be used, in which multiple functional fiber layers are simultaneously placed in a container containing a crosslinking matrix solution and immersed for a preset time to ensure that the crosslinking matrix solution can fully cover the surface of the functional fiber layers and initially penetrate into the fiber structure. This method is convenient to operate, efficient, and suitable for batch prepreg production.
[0077] For example, the crosslinking matrix solution can be an epoxy resin solution, a polyurethane solution, a silicone rubber solution, or a phenolic resin solution, etc. The viscosity, concentration, impregnation time, and pressurization time of the crosslinking matrix solution vary for different functional fiber layers.
[0078] Pre-curing refers to the initial curing of the functional fiber layer after prepreg, so that the cross-linked matrix undergoes a partial cross-linking reaction and forms a semi-cured state. The purpose is to fix the position of the cross-linked matrix in the functional fiber layer, prevent the cross-linked matrix from being lost during subsequent laying, and at the same time give the functional fiber semi-cured layer a certain degree of hardness to facilitate laying operations.
[0079] The functional fiber semi-cured layer is a pre-cured product, and its quantity is consistent with that of the functional fiber layer. It includes a fiber felt semi-cured layer, an interwoven fiber semi-cured layer, and a unidirectional fiber semi-cured layer, which are formed after prepreg and pre-curing, respectively corresponding to the fiber felt layer 201, interwoven fiber layer 202, and unidirectional fiber layer 203.
[0080] S2: The fiber felt semi-cured layer, the interlaced fiber semi-cured layer and the unidirectional fiber semi-cured layer are laid in the mold in the following order. The laying order includes the interlaced fiber semi-cured layer being stacked along the thickness direction on both sides of the fiber felt semi-cured layer, and the unidirectional fiber semi-cured layer being stacked along the thickness direction on both sides of the interlaced fiber semi-cured layer.
[0081] The mold is used to define the shape and size of the buffer structure 200. Its shape is adapted to the shape of the buffer structure 200. Depending on the shape of the box body 100, the mold can be a cuboid frame mold, a cylindrical ring mold, or an irregular polygonal frame mold, etc.
[0082] For example, the mold material can be a metal mold, a silicone mold, or a resin mold, wherein metal molds have high strength, high temperature resistance, and long service life, and are suitable for mass production.
[0083] In some examples, there are two specific ways to implement the laying sequence. The first method is to lay a unidirectional fiber semi-cured layer, an interlaced fiber semi-cured layer, a fiber mat semi-cured layer, an interlaced fiber semi-cured layer, and a unidirectional fiber semi-cured layer in sequence. That is, first lay a unidirectional fiber semi-cured layer at the bottom of the mold, then lay an interlaced fiber semi-cured layer on top of it, then lay a fiber mat semi-cured layer on top of the interlaced fiber semi-cured layer, then lay an interlaced fiber semi-cured layer on top of the fiber mat semi-cured layer, and finally lay a unidirectional fiber semi-cured layer on top of the interlaced fiber semi-cured layer, forming a symmetrical stacked structure. This method is convenient to lay, has uniform stress, and is suitable for most scenarios.
[0084] The second implementation method is symmetrical laying. First, a fiber felt semi-cured layer is laid in the center of the mold. Then, interlaced fiber semi-cured layers are laid simultaneously on both sides of the interlaced fiber semi-cured layer. Finally, a unidirectional fiber semi-cured layer is laid simultaneously on the outer sides of the two interlaced fiber semi-cured layers. This method ensures the symmetry of the stacked structure on both sides, avoids misalignment, and ensures uniform stress on the buffer structure 200. It is suitable for scenarios with high performance requirements for the buffer structure 200.
[0085] S3: Secondary curing, the cross-linked matrix of the fiber felt semi-cured layer, the interwoven fiber semi-cured layer and the unidirectional fiber semi-cured layer flows and permeates each other, and is compacted and connected under a preset pressure to form a buffer structure 200.
[0086] The secondary curing temperature is higher than the pre-curing temperature, which can accelerate the cross-linking reaction rate of the cross-linking matrix and ensure that the cross-linking matrix is completely cross-linked. In some examples, the secondary curing temperature is 100°C to 150°C. This temperature range can enable most cross-linking matrices to be completely cross-linked, while avoiding damage to the functional fiber layer due to excessive temperature.
[0087] In some examples, the secondary curing time is 30 to 60 minutes to ensure that the cross-linked matrix is fully cross-linked and that the semi-cured layers of each functional fiber are firmly connected.
[0088] The purpose of the preset pressure is to ensure tight adhesion of the semi-cured functional fiber layers, promote the flow and interpenetration of the cross-linked matrix, prevent gaps within the buffer structure 200, and improve the structural strength and density of the buffer structure 200. The preset pressure is adjusted according to the thickness and material type of the buffer structure 200. In some examples, the preset pressure range for secondary curing is 5-10 MPa.
[0089] The flow and interpenetration of the cross-linked matrix refers to the melting and flow of the semi-cured cross-linked matrix under the high temperature and preset pressure of secondary curing. It flows from the interior of each functional fiber semi-cured layer to the gaps between the layers, achieving interpenetration and forming a continuous adhesive system that firmly connects each functional fiber semi-cured layer into a whole.
[0090] S4: The buffer structure 200 is connected to the periphery of the box body 100 to form the box body of the battery device.
[0091] In this embodiment, through precise control of the entire process of prepreg, pre-curing, layered laying, and secondary curing, the gradient change in mass density of the fiber felt layer 201, interwoven fiber layer 202, and unidirectional fiber layer 203 can be ensured, achieving a uniform increasing distribution from the center to both sides, with a smooth gradient transition and no local density anomalies. Precise control of multiple functional fiber layers with different mass densities through prepreg improves the uniformity of mass density control for each functional fiber layer. First, pre-impregnating each functional fiber layer with a crosslinking matrix solution ensures that the crosslinking matrix evenly covers the surface of each fiber layer and fully penetrates into the internal pores of the fiber. This avoids defects such as uneven distribution of the crosslinking matrix and localized lack of adhesive during subsequent molding. It also lays the foundation for the uniformity of the mass density of each functional fiber layer, preventing local density fluctuations caused by matrix penetration deviations and ensuring the stability of the mass density gradient. The subsequent secondary curing process, under the synergistic effect of high temperature and preset pressure, allows the semi-cured crosslinking matrix to flow fully and permeate each other, firmly connecting the semi-cured functional fiber layers into a whole. This not only avoids problems such as peeling and delamination between fiber layers, but also further compacts the structure, ensuring the durability of the mass density gradient distribution, while reducing the surface porosity of the buffer structure.
[0092] Further, refer to Figure 5 In some optional embodiments of this application, before step S1, in which multiple functional fiber layer prepregs are placed in a crosslinking matrix solution and pre-cured, so that the crosslinking matrix crosslinks and fills the spaces between the functional fiber layers and permeates and connects the fiber structures in the functional fiber layers to form multiple functional fiber semi-cured layers, the method further includes: S0: Multiple functional fiber layers are subjected to plasma treatment in a mixed gas environment of inert gas and oxygen.
[0093] Plasma treatment refers to the plasma modification treatment of functional fiber layers by plasma treatment equipment. The core function of plasma treatment equipment is to generate plasma, so that the mixed gas reacts with the surface of the functional fiber layer under the action of plasma, thereby achieving surface activity modification of the fiber layer and improving the wetting effect of the cross-linked matrix.
[0094] For example, the types of plasma processing equipment include continuous plasma processing equipment, intermittent plasma processing equipment, etc.
[0095] A mixed gas refers to a gas system formed by mixing inert gas and oxygen in a preset ratio. It is used in plasma treatment processes. Its core function is to cooperate with plasma to modify the surface of functional fiber layers. The inert gas is used to protect the functional fiber layers from excessive oxidation, while the oxygen is used to introduce active groups to the surface of the fiber layers under the action of plasma.
[0096] The inert gases in the gas mixture include nitrogen, helium, and argon.
[0097] In some examples, the plasma processing power can be 300-500W, which can be flexibly adjusted according to the thickness of the fiber cloth. For example, 300-400W is used for 1.0-2.0mm fiber cloth, and 400-500W is used for 2.0-3.0mm fiber cloth.
[0098] The processing time is 10-15 minutes, a fixed duration, to ensure uniform surface modification of the fibers and avoid insufficient interfacial bonding due to too short a time or fiber damage due to too long a time.
[0099] In some examples, by adding a plasma treatment step before prepreg precuring, the surface properties of the functional fiber layers are effectively optimized, improving their compatibility and adhesion with the crosslinked matrix. This provides a good foundation for subsequent processes, thereby enhancing the stability of the preparation method and product quality. Specifically, the surface-active groups and slight roughness introduced by the plasma treatment promote full penetration and uniform adhesion of the crosslinked matrix, avoiding defects such as insufficient prepreg and interlayer lack of adhesive, ensuring that each functional fiber layer forms a strong whole with the crosslinked matrix. Simultaneously, the mixed environment of inert gas and oxygen protects the fiber layer properties from damage, ensuring that the high strength and high toughness advantages of the functional fiber layers are fully utilized, further improving the impact resistance, structural integrity, and stability of the buffer structure 200. This results in a 30% increase in the surface energy of the functional fiber layers and an adhesion strength of ≥18 MPa to the crosslinked matrix.
[0100] Furthermore, in some optional embodiments of this application, the volume ratio of inert gas to oxygen is 4:1; and / or, the inert gas is argon.
[0101] Limiting the volume ratio of inert gas to oxygen to 4:1 effectively balances the modification effect and fiber layer performance protection, avoiding defects caused by improper ratios: if the volume ratio of inert gas to oxygen is greater than 4:1, the oxygen content is insufficient, and enough active groups cannot be introduced into the fiber layer surface during plasma treatment, resulting in poor modification effect. The subsequent penetration and bonding strength of the cross-linked matrix will not be significantly improved, and the problem of weak interlayer adhesion will still exist. If the volume ratio of inert gas to oxygen is less than 4:1, the oxygen content is too high, which will cause the functional fiber layer surface to be over-oxidized, destroying the molecular structure of the fiber, leading to fiber layer embrittlement, decreased tensile strength, and affecting the impact resistance and structural strength of the buffer structure 200.
[0102] Argon has higher plasma activity, enabling it to work synergistically with oxygen at lower processing power to effectively modify the fiber layer surface, reduce the energy consumption of plasma processing, improve modification efficiency, shorten processing time, and meet the needs of mass production. Argon's chemical properties are extremely stable, which can more effectively isolate air, prevent the functional fiber layer from being oxidized during plasma processing, protect the original properties of the fiber layer, and ensure that it does not have any side reactions with the fiber layer or oxygen, thus ensuring the purity of the modification effect and preventing the introduction of impurities that may affect subsequent prepreg and curing processes.
[0103] Specifically, in the embodiments of this application, the pre-curing temperature is 60-80℃ and the pre-curing time is 15-25 minutes.
[0104] The pre-curing temperature is limited to 60-80℃. This temperature range has been precisely optimized to suit the reaction characteristics of cross-linked matrices such as modified epoxy resin. When the temperature is below 60℃, the cross-linking reaction rate of the cross-linked matrix is too slow. Even if the pre-curing time is extended, it is difficult to reach the expected semi-cured state. This will result in insufficient hardness of the functional fiber semi-cured layer, easy deformation during subsequent laying, easy loss of the cross-linked matrix, and increased difficulty in subsequent secondary curing, affecting the integrity of the buffer structure 200. When the temperature is above 80℃, the cross-linking reaction rate of the cross-linked matrix is too fast, which will lead to over-curing. The cross-linked matrix will be fully cross-linked in advance, and during subsequent secondary curing, it will be unable to flow and interpenetrate, failing to firmly connect the functional fiber semi-cured layers into a whole. This will lead to defects such as delamination and peeling inside the buffer structure 200, seriously affecting the buffering performance and structural strength.
[0105] For example, the pre-curing operation environment needs to be a constant temperature environment, usually using a constant temperature chamber for precise temperature control, with the temperature fluctuation range controlled within ±2℃, to ensure that the pre-curing effect of each functional fiber layer is uniform and consistent, and to avoid uneven pre-curing effect due to local temperature deviation, which would affect the overall performance of the buffer structure 200.
[0106] The pre-curing time is limited to 15-25 minutes, matching the temperature range of 60-80℃, to ensure that the cross-linking matrix undergoes an appropriate cross-linking reaction. If the time is less than 15 minutes, the cross-linking reaction is insufficient, the pre-curing is inadequate, the performance of the functional fiber semi-cured layer is unstable, and problems such as cross-linking matrix loss and weak interlayer adhesion are likely to occur. If the time is more than 25 minutes, the cross-linking reaction is excessive, the pre-curing effect exceeds the standard, which will not only affect the effect of subsequent secondary curing, but also increase production time, reduce production efficiency, increase production costs, and may cause problems such as embrittlement and cracking of the functional fiber semi-cured layer, affecting subsequent laying operations.
[0107] In some examples, the crosslinking matrix is a modified epoxy resin with an epoxy value of 0.4 eq / 100g (low viscosity), and the functional fiber layer is relatively thin (e.g., 0.4 mm for the fiber felt layer, 0.5 mm for the interwoven fiber layer, and 0.6 mm for the unidirectional fiber layer). Pre-curing at 60℃ for 15 minutes can be used to avoid over-curing and ensure the crosslinking matrix is properly fixed. In other examples, the crosslinking matrix is a modified epoxy resin with an epoxy value of 0.5 eq / 100g (moderate viscosity), and the functional fiber layer is a conventional epoxy resin. For standard thicknesses, a 70℃ constant temperature pre-curing for 20 minutes can be used, balancing pre-curing effect and production efficiency, making it suitable for mass production. In some examples, the crosslinking matrix is a modified epoxy resin with an epoxy value of 0.6 eq / 100g (high viscosity), and the functional fiber layer is thicker (e.g., 0.6 mm for the fiber felt layer, 0.7 mm for the interwoven fiber layer, and 0.8 mm for the unidirectional fiber layer). In these cases, a 80℃ constant temperature pre-curing for 25 minutes can be used to ensure sufficient crosslinking reaction, and the functional fiber semi-cured layer has sufficient hardness and toughness.
[0108] In this embodiment, by specifying the temperature and time parameters for pre-curing, the degree of cross-linking of the cross-linked matrix can be precisely controlled, ensuring a stable and consistent pre-curing effect and avoiding various defects caused by insufficient or excessive pre-curing. This allows the cross-linked matrix in the functional fiber layer after prepreg to undergo a partial cross-linking reaction, forming a semi-cured state. This serves two purposes: firstly, it fixes the position of the cross-linked matrix within the functional fiber layer, preventing loss and uneven penetration during subsequent laying; secondly, it gives the semi-cured functional fiber layer a certain degree of hardness and toughness, facilitating laying operations and ensuring precise alignment and tight adhesion of each layer, avoiding problems such as misalignment and excessive gaps.
[0109] Continue to refer to Figure 5 Furthermore, in an optional embodiment of this application, before connecting the buffer structure 200 to the periphery of the housing body 100 to form the battery device in step S3, the method further includes: S31: Apply an anti-corrosion coating to the outer periphery of the buffer structure 200.
[0110] For example, the material of the anti-corrosion coating can be polyurethane anti-corrosion coating, epoxy resin anti-corrosion coating, fluorocarbon anti-corrosion coating or polyvinyl chloride anti-corrosion coating. Among them, polyurethane anti-corrosion coating has excellent corrosion resistance, wear resistance and flexibility, can adapt to slight deformation of the buffer structure 200, is not easy to crack or fall off, and is suitable for most scenarios.
[0111] In some examples, the coating thickness needs to be controlled during the spraying process. Typically, the thickness of the anti-corrosion coating ranges from 0.1 to 0.3 mm. Too thin a coating will not achieve effective corrosion protection, while too thick a coating will increase the weight of the buffer structure, affecting lightweight requirements and potentially causing the coating to crack. After spraying, the anti-corrosion coating needs to be dried and cured. Drying and curing can be carried out at room temperature or accelerated under a constant temperature environment. Room temperature drying and curing takes 2-4 hours, while constant temperature drying and curing takes 30-60 minutes at a temperature controlled at 60-80℃, ensuring complete drying and curing to form a strong protective layer.
[0112] The mechanical impact test passed GB / T 2423.55-2016, showing a 50% increase in energy absorption rate; after 1000 hours of salt spray testing, no corrosion was observed, and the strength retention rate of the buffer structure 200 was >95%. The salt spray test can be conducted using GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test" or GB / T 2423.17-2024 "Environmental Testing - Part 2: Test Methods - Test Ka: Salt Spray".
[0113] If the buffer structure 200 is connected to the box body 100 before the anti-corrosion coating is applied, the connection between the buffer structure 200 and the box body 100 will not be covered by the anti-corrosion coating, forming a blind spot for corrosion protection. External corrosive media (such as moisture, salt spray, chemical ions, etc.) will enter through this blind spot, causing corrosion of the buffer structure 200 and the box body 100, affecting their service life. However, if the anti-corrosion coating is applied first and then the connection is made, it can ensure that the outer circumference of the buffer structure 200 is fully covered by the anti-corrosion coating, without dead corners or blind spots. At the same time, the connection can be further improved through subsequent sealing treatment, forming a complete anti-corrosion system.
[0114] The above are merely specific embodiments of this application. Those skilled in the art will clearly understand that, for the sake of convenience and brevity, the specific working processes of the systems, modules, and units described above can be referred to the corresponding processes in the foregoing method embodiments, and will not be repeated here. It should be understood that the protection scope of this application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this application, and these modifications or substitutions should all be covered within the protection scope of this application.
Claims
1. A housing for a battery device, characterized in that, include: The box body and the buffer structure are connected to the periphery of the box body; The buffer structure includes a cross-linked matrix and multiple functional fiber layers. The cross-linked matrix fills the spaces between the functional fiber layers and permeates and connects to the fiber structures within each functional fiber layer. The multiple functional fiber layers include a fiber felt layer, an interlaced fiber layer, and a unidirectional fiber layer. The interlaced fiber layer is stacked along the thickness direction on both sides of the fiber felt layer, and the unidirectional fiber layer is stacked along the thickness direction on both sides of the interlaced fiber layer. The mass density of the fiber felt layer, the interlaced fiber layer, and the unidirectional fiber layer increases sequentially. The fiber volume content of the buffer structure is 50-60%.
2. The housing of the battery device according to claim 1, characterized in that, The mass density of each layer in the fiber felt layer, the interwoven fiber layer, and the unidirectional fiber layer ranges from 0.8 g / cm³ to 3.5 g / cm³.
3. The housing of the battery device according to claim 2, characterized in that, The mass density of the fiber felt layer ranges from 1.25 g / cm³ to 0.8 g / cm³; the mass density of the interwoven fiber layer ranges from 1.5 g / cm³ to 1.8 g / cm³; and the mass density of the unidirectional fiber layer ranges from 1.85 g / cm³ to 3.5 g / cm³.
4. The housing of the battery device according to any one of claims 1 to 3, characterized in that, The thickness of the buffer structure ranges from 1 mm to 3 mm; And / or, The thickness of the fiber felt layer ranges from 0.4 mm to 0.6 mm; the thickness of the interwoven fiber layer ranges from 0.5 mm to 0.7 mm; and the thickness of the unidirectional fiber layer ranges from 0.6 mm to 0.8 mm.
5. The housing of the battery device according to any one of claims 1 to 3, characterized in that, The volume fraction of the surface porosity of the buffer structure is between 1% and 2%, and the pore size is less than or equal to 0.1 micrometers.
6. A method for manufacturing the housing of a battery device according to any one of claims 1 to 5, characterized in that, include: Multiple functional fiber layer prepregs are placed in a crosslinking matrix solution and pre-cured, so that the crosslinking matrix crosslinks and fills the fiber structure between each functional fiber layer and permeates and connects to each functional fiber layer, forming multiple functional fiber semi-cured layers. The multiple functional fiber semi-cured layers include fiber felt semi-cured layers with progressively increasing mass density, interwoven fiber semi-cured layers, and unidirectional fiber semi-cured layers. The fiber felt semi-cured layer, the interlaced fiber semi-cured layer and the unidirectional fiber semi-cured layer are laid in the mold in a laying sequence, wherein the laying sequence includes the interlaced fiber semi-cured layer being stacked along the thickness direction on both sides of the fiber felt semi-cured layer, and the unidirectional fiber semi-cured layer being stacked along the thickness direction on both sides of the interlaced fiber semi-cured layer. Secondary curing involves allowing the cross-linked matrix of the fiber felt semi-cured layer, the interwoven fiber semi-cured layer, and the unidirectional fiber semi-cured layer to flow and permeate each other, and then compacting and connecting them under a preset pressure to form a buffer structure. The buffer structure is connected to the periphery of the box body to form the box body of the battery device.
7. The method for preparing the housing of the battery device according to claim 6, characterized in that, Before the step of pre-curing multiple functional fiber layers in a crosslinking matrix solution, thereby crosslinking and filling the fiber structures between and penetrating the functional fiber layers to form multiple functional fiber semi-cured layers, the method further includes: Multiple functional fiber layers were subjected to plasma treatment in a mixed gas environment of inert gas and oxygen.
8. The method for preparing the housing of the battery device according to claim 7, characterized in that, The volume ratio of the inert gas to the oxygen is 4:1; And / or, the inert gas is argon.
9. The method for preparing the housing of the battery device according to claim 6, characterized in that, The pre-curing temperature is 60-80℃, and the pre-curing time is 15-25 minutes.
10. The method for preparing the housing of the battery device according to claim 6, characterized in that, Before connecting the buffer structure to the periphery of the housing body to form the battery device, the method further includes: An anti-corrosion coating is sprayed onto the outer peripheral surface of the buffer structure.
Citation Information
Patent Citations
High-toughness copper-clad plate and preparation method thereof
CN107696646A
High-impact-resistant thermoplastic composite bottom protective plate
CN119283467A
Fracture-resistant polypropylene plate and preparation method thereof
CN119928379A